A new algorithm for the management of diabetic foot ulcer: recommendations from Central and Eastern Europe. (2nd May 2023) - Bem, Robert; Chadwick, Paul; Cvjetko, Ivan; Koliba, Miroslav; Kokeny, Zoltan; Lipinski, Przemyslaw; Mrozikiewicz-Rakowska, Beata; Rozsos, Istvan; Wegrzynowski, Adam
Abstract : There is wide regional variation in clinical practice and access to treatment for patients with diabetic foot ulcer (DFU) from countries in Central and Eastern Europe (CEE). A treatment algorithm that reflects current treatment practices while providing a common framework may facilitate best practice in DFU management and improve outcomes across the CEE region. Following a series of regional advisory board meetings with experts from Poland, the Czech Republic, Hungary and Croatia, we present consensus recommendations for the management of DFU and outline the key features of a unified algorithm for dissemination and use as a quick tool in clinical practice in CEE. The algorithm should be accessible to specialists as well as non-specialist clinicians and should incorporate: patient screening; checkpoints for assessment and referral; triggers of treatment change; and strategies for infection control, wound bed preparation and offloading. Among adjunctive treatments in DFU, there is a clear role for topical oxygen therapy, which can be used concomitantly with most existing treatment regimens in hard-to-heal wounds following standard of care. Countries from CEE face a number of challenges in the management of DFU. It is hoped that such an algorithm will help standardise the approach to DFU management and overcome some of these challenges. Ultimately, a regionwide treatment algorithm in CEE has the potential to improve clinical outcomes and save limbs.